Multiple Cranial Nerve Palsies as the First Presentation of Sarcoidosis - Oliver Rose; Zahoor Ahmad; Barry Snow (Case Reports in Otolaryngology)
Sarcoidosis is a disease process which predominantly affects the lungs but can involve virtually any organ in the human body. Neurosarcoidosis is a rare manifestation which can present in a variety of ways. There is no single diagnostic test for sarcoidosis; hence, the diagnosis is based on combined clinical, laboratorial, and radiological grounds. We describe a rare case where a patient presented with dysphagia, hoarseness, hearing loss, and unsteadiness.